Uptake and transport mechanisms for cadmium by Myriophyllum aquaticum in a constructed wetland - Huang, Zhenzhen; Gao, Jingqing; Zhao, Geran; He, Jie; Mao, Yanli; Kang, Haiyan; Song, Zhongxian (Ecotoxicology and environmental safety, 2024)
Myriophyllum aquaticum (M. aquaticum), as a Cd-highly enriched and tolerant species, has greater application in phytoremediation of Cd-polluted waters. Mechanisms of Cd uptake and transport of M. aquaticum were comprehensively investigated in this work. Transport direction of Cd was observed both from the roots to the aboveground and vice versa. The aboveground can be harvested during vigorous growth and flowering periods, further improving the efficient phytoremediation of Cd-polluted wastewater. Moreover, analysis of transpiration inhibition, low-temperature treatment and metabolic inhibition indicated that the uptake and transport of Cd by M. aquaticum can be achieved via the coexistence of the free diffusion-dominated apoplast pathway dominated by transpiration and the "cellular pathway" dominated by active absorption, with the active energy-demanding cellular pathway playing a dominant role. The obtained results have important implications in the in-depth exploration of uptake, transport and distribution mechanisms of heavy metals during phytoremediation of aquatic plants. [Display omitted] •Transport direction of Cd was observed both from the roots to the aboveground and vice versa.•M. aquaticum had higher capacity for aboveground uptake and transport of Cd in vigorous growth and flowering periods.•Harvest of the aboveground of M. aquaticum during critical periods can improve the phytoremediation efficiency of Cd.•Cd uptake and transport of M. aquaticum were dominated by the active energy-demanding cellular pathway.